EFFICIENT OTP GENERATION WITH ENCRYPTION AND DECRYPTION FOR SECURE FILE ACCESS IN CLOUD ENVIRONMENT - R, Manjupargavi; M.V., Srinath (ICTACT journal on communication technology, 2022)
Cloud Computing (CC) has grown increasingly important in recent years, and the security issues related to the cloud model are also on the rise. The most used computer system authentication mechanism is One Time Password (OTP) which is easier and more successful than other techniques while being subject to assaults such as eavesdropping and replay attacks. This study proposes the use of the OTP mechanism to tackle this problem. The user must utilize the OTP provided by the cloud environment, which is produced using the random function, to strengthen the security of data retrieval from the cloud. Documents may be safeguarded against unauthorized users using this OTP (secret key) generation or creation mechanism. Then it offers data encryption, which safeguards data files from a cloud provider. To encrypt the file, the cryptography library uses a symmetric approach based on the same key to encrypt and decode the file. The cryptography packages have been introduced in this work to provide built-in functions for key generation, cipher text encryption, and cipher text decryptions utilizing both encrypt and decrypt methodologies. The fernet module ensures that data encrypted with it cannot be edited or read if the key is not there. This will make it easier to exchange public data with other cloud users who have been verified. The processing time for secure authentication with OTP creation using 4, 6, 8, and 10 digits is reduced to 0.0016, 0.0028, 0.0035, and 0.0042 seconds, respectively, while the elapsed time for Encryption and Decryption algorithms such as Reverse Cipher, Caesar Cipher, and ROT13 is 0.00025, 0.00065, and 0.00207s.